Compositional methods of music therapy - Jackson, Nancy; Heiderscheit, Annie (Barcelona Publishers, 2022)
Selecting and designing appropriate and effective music therapy experiences involves a critical thought process that considers multiple aspects of the client and their personal, interpersonal, and therapeutic contexts, as well as the nature of the four music therapy methods. Compositional Methods in Music Therapy focuses specifically on procedural guidelines for the compositional method-variations. Case illustrations examine the thought process leading to clinical decisions about the selection of music experiences that are based on the needs of clients and the affordances inherent in music composition. General guidelines for planning and implementing are provided in the form of questions that encourage critical thinking and creativity and which allow understanding of the client to be incorporated into the music therapist's preparation for sessions. Approaching music therapy planning in this manner provides the foundation for practice that is based in music engagement and makes full use of the potential of music to be transformational in people's health and well-being. This book is intended for use by pre-internship music therapy students and by professionals who have never approached music therapy planning and implementation from the perspective of the four methods. It is designed to be used either in whole from front to back or in parts in any order in relation to a course or to an individual's learning needs. Illustrative material is provided to solidify understanding, as well as to connect readers with other resources they can seek out on their own. Compositional Methods in Music Therapy is one in a series of texts addressing each of the four music therapy methods.
Keywords: Music therapy